The Codification of Hadith in the Third Century of Hijriah as the Peak of the Golden Age of Knowledge - Mustikawati; Muhammad Al Mighwar; Engkos Kosasih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper examines matters related to the growth and bookkeeping of hadith in the 3rd century AH which is the pinnacle of science. This article discusses several things including the meaning of codification, the activities of hadith scholars, the codification pattern of hadith. The preparation of hadith books was not very significant during the time of the Companions because it was feared that the Qur'an and the hadith would be mixed. It was only in the 2nd century that it was written because there were many false hadiths circulating. And continued in the 3rd century which was a golden age in bookkeeping because of the development of the bookkeeping of the hadith. The method used is library research, which is a literature study with a historical approach. The results of the study show that in the 3rd century AH the development of hadith codification was the peak and became the golden age of science with the existence of books that emerged such as sahih Bukhari.